Don't Simplify, Complexify: From Disjunctive to Conjunctive Theorizing in Organization and Management Studies - Tsoukas, Haridimos (Journal of Management Studies, 2017)
ABSTRACTIn this paper I argue that, rather than theory development aim at simplifying complex organizational phenomena, it should aim at complexifying theories – theoretical complexity is needed to account for organizational complexity. Defining the latter as the capacity for ‘nontrivial’ action, I explore a complex ‘system of picturing’ organizations as objects of study that provides an alternative to the hitherto dominant disjunctive style of thinking. A complex ‘system of picturing’ consists of an open‐world ontology, a performative epistemology, and a poetic praxeology. Complex theorizing is conjunctive: it seeks to make connections between diverse elements of human experience through making those analytical distinctions that will enable the joining up of concepts normally used in a compartmentalized manner. Insofar as conjunctive theorizing is driven by the need to preserve the ‘living‐forward – understanding backward’ dialectic, it is better suited to grasping the logic of practice and, thus, to doing justice to organizational complexity. We come close to grasping complexity when we restore the past to its own present and make distinctions that overcome dualisms, preserving as much as possible relationality, temporality, situatedness and, interpretive open‐endedness. I illustrate the argument with several examples from organizational and management research.